Upaya Pemberantasan Kartel dengan Pemberlakuan Leniency Program - Marifa Anandita Sari (Jurnal Ilmiah Mandala Education (JIME), 2020)
This research is intended to explain whether the leniency program can be applied in Indonesia. In accordance with Law No. 5 of 1999, Indonesia currently has not implemented a leniency program in terms of cartel empowerment efforts. The Leniency Program is expected to be a solution to reduce and be able to open a veil of cartel that has been difficult to prove. Research method in this paper using normative method with the analysis of regulations and comparative law. The results of this study show that the leniency program that has been launched by the developed state can reduce and open cartel cases significantly. Even so, the application needs to be considered according to the needs of the country. In a number of other studies, developing countries that apply the leniency program only duplicate those that have been implemented by other countries so that their application is less effective. The amendment to the competition law is needed to applied leniency program